High-speed multicolour photometry with CMOS cameras - Pokhvala, S.M.; Zhilyaev, B.E.; Reshetnyk, V.M. (Advances in Astronomy and Space Physics, 2012)
We present the results of testing the commercial digital camera Nikon D90 with a CMOS sensor for high-speed photometry with a small telescope Celestron 11ʺ at the Peak Terskol Observatory. CMOS sensor allows to perform photometry in 3 filters simultaneously that gives a great advantage compared with monochrome CCD detectors. The Bayer BGR colour system of CMOS sensors is close to the Johnson BVR system. The results of testing show that one can carry out photometric measurements with CMOS cameras for stars with the V-magnitude up to ≃14ᵐ with the precision of 0.01ᵐ. Stars with the V-magnitude up to ∼10 can be shot at 24 frames per second in the video mode.